Pengaruh Kualitas Layanan, Kualitas Properti Dan Kepuasan Pelanggan Terhadap Minat Sewa Rumah Kontrakan Griya Harapan Kota Pekanbaru - Rianda, Muhammad; Setyawati, Novita Ayu; Sumantyo, Fransiscus Dwikotjo Sri (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This research investigates the impact of service quality, property quality, and customer satisfaction on the interest in renting contracted houses at Griya Harapan, pekanbaru City. Adopting a quantitative approach, data were gathered via questionnaires distributed to 92 respondents who are current tenants. The findings, analyzed through Partial Least Squares Structural Equation Modeling (PLS-SEM), reveal that customer satisfaction and property quality significantly influence rental interest, while service quality does not show a significant effect. These results highlight the necessity of upholding high property standards and ensuring customer satisfaction to boost rental interest. This study aims to assist property managers in developing more effective marketing strategies.